Genotoxic potential of the air in environments with photocopiers - Filipini, Gedalva Teresinha; Leite, André Búrigo; Techio, Vânia Helena (Revista Brasileira de Biociências, 2009)
In environments with photocopiers, among the monitored contaminants, there are the volatile organic compounds (VOCs), aromatic polycyclic hydrocarbons, aldehydes, ketones, ozone, and particles. The present study aimed at the assessment of the genotoxicity of the air in environments with photocopiers. Six clones of Tradescantia (4430) had been kept for 15 days in two environments – one of them with four photocopiers working 12 hours per day, and the other with three photocopiers working 8 hours per day. Other six plants comprised the check group and were kept in greenhouse. The frequency of genic and chromosomal mutations was determined through the assessment of the stamen hair cells, and tetrads, respectively, performed 15 days after the exposition. There were quantified 415 stamen hairs and 1,500 tetrads per treatment. The plants from treatment 1 – exposed to daily cycles of 12 hours with 4 photocopiers – have presented the highest frequency of chromosomal damage with significant differences in relation to the check group (p< 0.01). No significant difference was observed in the stamen hairs for genic mutation in relation to the check group.